DATA PROCESSING DESIGN PAYROLL PT. NUSA PERSADA - Kutni Kutni; Yuce Yuliani. Skom. MM (Jurnal Sistem Informasi, 2000)
Based on the discussions that have been described in this writing, PT. Nusa Persadanot using payroll systems and procedures are good, as seen in the absence of flow ofauthority and proper authorization system as a normal procedure in many companies.Use of computers in data processing payroll enormous advantages, both in speed,keteletian and in terms of research. Besides the other benefits of using computertechnology in managing the payroll very easily and quickly browse the event of anerror in the listing, can create reports quickly when needed at any time, storage ofcritical data will be safer.